A characterization study of testing contributors and their contributions in open source projects - Souza, Hugo Henrique Fumero de; Wiese, Igor; Steinmacher, Igor; Ré, Reginaldo (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2022: Anais do XXXVI Simpósio Brasileiro de Engenharia de Software, 2022)
Even though open source projects have some different characteristics from projects in the industry, the commitment of maintainers and contributors to achieve a high level of software quality is constant. Therefore, tests are among the main practices of the communities. Thus, motivating contributors to write new tests and maintain regression tests during testing activities is essential for the project’s health. The objective of our work is to characterize testers and their contributions to open source projects as part of a broad study about testers’ motivation. Thus, we conducted a study with 3,936 repositories and 7 different and important programming languages (C, C++, C#, Java, Javascript, Python, and Ruby), analyzing a total of 4,409,142 contributions to classify contributing members and their contributions. Our results show that test-only contributors exist, regardless of programming language or project. We conclude that, despite the unfavorable scenario, there are contributors who feel motivated and dedicate their time and effort to contribute to new tests or to the evolution of existing tests.